Mdm2 antagonists induce apoptosis and synergize with cisplatin overcoming chemoresistance in TP53 wild‐type ovarian cancer cells. Issue 7 (11th October 2012) - Mir, Roser; Tortosa, Avelina; Martinez‐Soler, Fina; Vidal, August; Condom, Enric; Pérez‐Perarnau, Alba; Ruiz‐Larroya, Tatiana; Gil, Joan; Giménez‐Bonafé, Pepita
Abstract Ovarian cancer (OVCa) is the leading cause of death from gynecological malignancies. Although treatment for advanced OVCa has improved with the introduction of taxane–platinum chemotherapy, the majority of patients will develop resistance to the treatment, leading to poor prognosis. One of the causes of chemoresistance is the reduced ability to undergo apoptosis. Cisplatin is a genotoxic drug that leads cells to apoptosis through the activation of the p53 pathway. Defective signaling in this pathway compromises p53 function, and thus cisplatin does not induce apoptosis. A new group of nongenotoxic small molecules called Nutlins have been developed to inhibit p53‐Mdm2 binding, inducing apoptosis in chemoresistant tumors through the activation of the p53 pathway. The wild‐type p53 cisplatin‐resistant ovarian cancer cell‐line A2780cis was used to test the effect of Nutlin‐3a (Nut3a) on apoptosis response. The results showed that Nut3a synergized with cisplatin, inducing cell‐cycle arrest in G2/M and potentiating apoptotic cell death. Increased apoptosis was also induced in wild‐type TP53 primary OVCa cultures by double cisplatin–Nut3a treatment. In conclusion, Nut3a appears to sensitize chemoresistant OVCa cells to cisplatin, inducing apoptosis. As increased response was generalized in primary tumors, this cisplatin–Nut3a combination could be useful for the treatment of patients harboring wild‐type TP53 who do not respond to standard chemotherapy.